Is molecular hydrogen beneficial to enhance post-exercise recovery in female athletes? - Drid, P.; Trivic, T.; Casals, C.; Trivic, S.; Stojanovic, M.; Ostojic, S. M. (Science & Sports, 2016)
Objectives: The purpose of this double-blind, randomized, placebo-controlled crossover study was to determine the effects of pre-exercise hydrogen-rich water intake on biomarkers of acid-base homeostasis and post-exercise recovery in female athletes. Methods: Eight young female judo athletes (21.4 ± 2.2 years) were randomly assigned to receive either hydrogen-rich water or placebo water ~ 30 minutes before exercise. The same procedures were repeated 4 days after the first assessment in a crossover design. The exercise protocol consisted of high-intensity inttermitent exercise by means of a judo-specific test. Heart rate was recorded at baseline and post-exercise. Participants` blood was sampled in order to determine the arterial blood pH, bicarbonates and lactates at rest (prior to the intervention), 3 minutes and 5 minutes post-exercise. Results: Hydrogen-rich water significantly affected post-exercise blood pH and lactates as compared to the placebo (P < 0.05), while serum bicarbonate responses did not differ between interventions. No differences were found between hydrogen-rich water and placebo in heart rate responses to exercise. No side effects of either intervention were noted. Conclusion: Hydrogen-rich water might be an appropriate and safe hydration strategy that helps athletes to become less susceptible to exercise-induced acidosis.